(untitled) (Journal of Musikot Campus, 2024)
The aim of this study was to find the social work students’ perceptions of Information and Communication Technology (ICT) in their educational experiences, focusing on performance expectancy, technology acceptance, attitudes toward ICT, and its relevance and practicality. This study adopted a survey research design under a quantitative research approach. The study reveals that students generally be aware of the substantial benefits of ICT in enhancing educational quality, facilitating access to information, and connecting academic learning with real-life applications. A significant majority agree that ICT-equipped classrooms and instructional aids improve teaching and learning, though some students express concerns about potential distractions and challenges in using technology effectively. Findings indicate a strong interest among students in developing their ICT skills and an acknowledgment of the necessity of these skills for academic and professional success. However, there are mixed perceptions about the ease of using ICT tools, with some students finding them challenging. The study also highlights the need for effective classroom management and targeted support to address these challenges.